PENINGKATAN PEMBELAJARAN GEOGRAFI DENGAN PENDEKATAN KREATIVITAS DI SMP NEGERI 3 PINRANG - SUTRAFATMA, SUTRAFATMA (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2015)
Success and learning geography is not confined to the work produced, but also on the process. In addition it is no less substantial is to utilize the ratings as feedback to improve student learning and evaluation is seen as an ongoing activity that is multidimensional. The new student work produced 25.5% met the criteria expected and 57.1% met most. Explanation of the assignment of teachers can not be accepted/well understood. Most of the students at the beginning of the task is still difficult. Assessment process applying various criteria can not be implemented properly as planned. Providing motivation and guidance and teacher, so pay attention to the theme of the image (free, preferably, imaginative) control of what should be delivered in early activity so that more effective learning. Need examples of the finished image (printed works) with a variety of puffs as props concrete so that students easily understand work instructions, as well as a creative example of appreciation. Provided a variety of liquid color and other media such as (crayons, pencils, colors, markers) that is scheduled to run smoothly. The collected works of regulated lined, so it can be evaluated properly. Learning concludes by providing information in general and specific assessment of the success shown students, suggestions and further motivation to work better for students.